2014
DOI: 10.1136/bjsports-2014-093989
|View full text |Cite
|
Sign up to set email alerts
|

Lipids, adiposity and tendinopathy: is there a mechanistic link? Critical review

Abstract: Being overweight or obese is associated with an elevated risk of tendon pathology. However, for sportspeople the epidemiological data linking weight or adiposity on one hand, and risk of tendon pathology on the other, are less consistent. Indeed, the mechanistic links between diet, adiposity and tendon pathology remain largely unexamined. Recent studies have begun to examine the effects of dietary interventions on outcomes such as tendon biomechanics or pain. Oxidised low-density lipoprotein has been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 51 publications
2
50
0
3
Order By: Relevance
“…Gaida et al have questioned whether the higher risk of tendinopathy associated with diabetes is caused by a disturbance in glucose metabolism per se. They proposed that the higher risk might have to be attributed to the overweight associated with diabetes [ 30 , 31 ]. The influence of overweight on tendinopathy has been explained in two different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Gaida et al have questioned whether the higher risk of tendinopathy associated with diabetes is caused by a disturbance in glucose metabolism per se. They proposed that the higher risk might have to be attributed to the overweight associated with diabetes [ 30 , 31 ]. The influence of overweight on tendinopathy has been explained in two different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the average BMI of people with diabetes is as high as 30 kg/m 2 (ie, obese),61 suggesting high baseline levels of adiposity in people with diabetes. There is evidence for an association between tendinopathy and adiposity so this may be another important possible confounder 5 65 66…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have identified an association between waist circumference and tendon pathology, 25 with preliminary evidence supporting either a mechanical effect (due to increased load) or systemic effect (due to circulating lipids). 26 The influence of adiposity on localized musculo-tendinous tissues in neuromuscular disorders will be an important factor to evaluate with the increasing rates of obesity in society.…”
Section: Resultsmentioning
confidence: 99%